Pengaruh Desain Produk, Harga Dan Brand Ambassador Terhadap Keputusan Pembelian Pada Konsumen Portee Di Jawa Barat - Solihah, Nita; Siddiqa, Heidi; Ardhiansyah (Jurnal Ekonomi Bisnis dan Manajemen, 2025)
This study aims to determine and analyze the influence of product design, price, and brand ambassador on consumers’ purchasing decisions for Portee brand shoes in West Java. The research employed a quantitative approach using a survey method. Data were collected from 100 respondents selected through purposive sampling. The analytical tools used in this study include multiple linear regression, classical assumption tests, and hypothesis testing with the assistance of SPSS version 25. The results showed that product design, price, and brand ambassador have a significant effect on purchasing decisions, both partially and simultaneously. These findings indicate that an attractive product design, competitive pricing, and a credible brand ambassador can strengthen consumer interest and influence their purchasing behavior. The research provides valuable insights for Portee producers to improve their marketing strategies through design innovation, appropriate pricing policies, and the selection of brand ambassadors that match consumer preferences.